Lateral epitaxial overgrowth and reduction in defect density of 3C-SiC on patterned Si substrates - Bushroa, A.R.; Jacob, C.; Saijo, H.; Nishino, S. (Elsevier, 2004)
Selective growth and reduction of defects of cubic silicon carbide (3C-SiC) crystals grown within windows and laterally over SiO2 masks patterned on Si substrates are presented. The growth has been performed via chemical vapor deposition using hexachlorodisilane and propane, as well as hexamethyldisilane. Lateral epitaxial overgrowth (LEO) was achieved at selected areas where windows are square or array of stripes. The LEO process was characterized mainly by atomic force microscopy.